Pengaruh lama pengapuran terhadap kadar protein, kadar lemak, dan rendemen pada kerupuk kulit Domba Rote - Robertus Yofantus; Bastari Sabtu; Dewi Elfrida Sihombing (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2026)
This study aims to determine the effect of limming time on protein content, fat content and yield in Rote sheepskin crackers. The skin used in this study is the skin from fresh Rote sheep which is used as research material. This study used an experimental method with a Complete Random Design (RAL) design consisting of three treatments and 5 replicates. The treatment is P1: limming duration is 150 minutes, P2: limming duration is 180 minutes and P3: limming duration is 210 minutes and each treatment gets 5 repeats. The variables tested were protein levels, fat levels, and yield. Cracker data on protein content, fat content and yield in the analysis using Analysis of Variance (ANOVA) and continued the Duncan test. The results of the study showed that the duration of liming had a very real effect (P<0.01) on the yield where the longer the liming of the yield decreased. The length of limming has a significant effect (P<0.05) on fat levels where fat levels increase in limming is higher. Meanwhile, the limming  period had no real effect (P<0.05) on protein levels. Based on the results of the study, it can be concluded that the soaking time has an effect on the fat content and yield of Rote sheepskin crackers, while the protein content is relatively unaffected. High limming time increases fat content but tends to lower yield, so it is necessary to optimize the length of limming time in the process of making Rote sheepskin crackers.